CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE AND OWNERSHIP STRUCTURE: MODERATING EFFECT OF ENVIRONMENTAL PERFORMANCE - Pricilia Sukarno Putri; Bambang Hadinugroho (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2023)
Using environmental performance as a moderating variable, we examine how ownership structure affects corporate social responsibility disclosure (CSR Disclosure). With a population of 124 BEI manufacturing sector enterprises, data was gathered through the documentation method from annual reports for the 2017–2021 period. A purposive sample of 24 companies was selected for the sample. However, analytical methods like moderated regression analysis (MRA) are employed. The results demonstrate that while management ownership harms CSRD, institutional and public ownership have a favorable impact on CSR Disclosure. The impact of institutional and public ownership on CSR disclosure is well moderated by environmental performance; however, the influence of management ownership on CSR disclosure is not successfully moderated. The outcomes of the control variables show that firm size and profitability are significant. However, leverage shows an insignificant result.